Analysis of the Language and Speech Portrait of an Literary Character - Axmetjanovna, Yunusova Aziza (Miasto Przyszłości, 2023)
The literary character - the bearer of imagery - is a speech creation and reflection of the image of the author, the personification of his idea of the world and himself. This article studies the issue of the linguistic and speech portrait of a literary character, which is an actual topic of studies in modern linguistics.